Wood anatomical features of Juniperus squamata Buch.-Ham. ex. D. Don from high mountains of Trans-Himalayan Zone of central Nepal - Chalise, Pratikshya; Tiwari, Achyut (Banko Janakari, 2024)
Wood anatomical characters were investigated for Juniperus squamata Buch.-Ham. ex. D. Don from high mountains of Trans-Himalayan Zone of Manang District of Central Nepal. We studied the anatomical features and the inter-relationship between the anatomical parameters of Himalayan Juniper from 30 different wood samples collected at 4600 m above the mean sea level (msl). Wood samples were boiled at 100ºC in oven, and sectioning was done using the KD-3390 Semi-automatic Microtome. The sections were then dehydrated in alcohol stained with 1% Safranin and fast green solutions, and permanent slides were prepared and observed under microscope. J. squamata is a softwood species and is characterized by the presence of distinct narrow annual growth rings with gradual to abrupt transition from earlywood to latewood. Both earlywood and latewood tracheids comprising square to polygonal cells, circular bordered pits and few resin cells arranged in loose tangential bands. The rays were found to be exclusively uniseriate and homogenous; most of the ray cells contained prismatic crystals while cupressoid pits were present in the ray cells.The annual-ring-width showed a positive correlation with both the earlywood and latewood width but a negative correlation with tracheids length. In softwood species like Junipers, tracheid length is an important characteristic, not only for wood and fiber quality, but also for the tree's hydraulic architecture. Furthermore, this is also coupled with the acclimatization of the species in harsh climatic condition of the arid trans-Himalayan region. Dwarf individuals with reduced growth ring dimensions and increased tracheid length ensure effective water transportation towards the shoot system. Therefore, this intra-specific variation in wood anatomical features of J.squamata is due to variation in micro-habitat types.